Analysis of Factors Causing Logistics Warehouse Inventory Mismatch at PT Dai Nippon Printing Indonesia - Sugiarto, Mandar; Suprayitno, Degdo (Yayasan Sinergi Kawula Muda, 2023)
This research was conducted at PT Dai Nippon Printing Indonesia. The purpose of this study is to determine the factors causing the mismatch of logistics warehouse inventory at PT Dai Nippon Printing Indonesia. In this study researchers conducted interviews. The research methodology used in this study is the litative research method. The results of the study stated that there are several factors that cause the discrepancy of logistics warehouses, including Man, Machine, Method, Material, Environment. Improvements that can be made to minimize inventory discrepancies in the logistics warehouse of PT Dai Nippon Printing Indonesia Pulogadung Factory include training or training for each employee and rolling work, rejuvenating transportation equipment and repairing network servers, ensuring goods entering logistics are well administrated, making special areas of problematic materials and creating a comfortable work environment for each employee.